Minireview: Silver-Doped Titanium Dioxide and Silver-Doped Zinc Oxide Photocatalysts. (13th April 2018) - Din, Muhammad Imran; Khalid, Rida; Hussain, Zaib
ABSTRACT: The catalytic oxidation of organic dyes using various systems has been widely reported during the past decade. Photocatalytic methods, heterogeneous processes for the degradation of dyes, are one of the best and efficient oxidation processes to treat industrial wastewater with minimal residual waste. This review describes the improvement in catalytic activity of silver-doped titanium dioxide and silver-doped zinc oxide. The degradation of dyes provides information about the catalytic performance of silver-doped metal oxide. The effects of pH, catalyst concentration, dye concentration, hydrogen peroxide, dissolved oxygen, temperature, irradiation time, and light source have been reviewed along with the degradation mechanism and reaction methodology of organic dyes.